Evaluasi Potensi Tumbuh Benih 21 Varietas Padi melalui Analisis Principal Component Analysis (PCA) dan Korelasi - M. Izhar; Munawarrah Munawarrah; Samsul Ma’arif; Dela Arinda (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Seed quality is a key factor in determining the success of germination and productivity of rice plants. This study aims to evaluate the seed growth potential of 21 rice varieties (Oryza sativa L.) consisting of local, national, and introduced varieties through correlation analysis and Principal Component Analysis (PCA). Four parameters observed include Maximum Growth Potential (PMP), Germination Power (DB), Plumule Length (PP), and Radicle Length (PR). The study was conducted at the Biology Laboratory, Satya Terra Bhinneka University, using a completely randomized design with three replications. The analysis results showed significant variations among varieties for all observed parameters. The PCA value showed that two principal components (PC1 and PC2) explained 78.1% of the total variability. The PTM and DB parameters had high negative loadings on PC1, indicating that this component represents seed viability, while PP and PR had positive loadings on PC2, which described the morphological vigor of the seedlings. The Sigupai, Tinggong, and Inpago 12 varieties were in the quadrant with negative PC1 and positive PC2 values, indicating a combination of high viability and strong seedling growth. Correlation analysis showed a very strong positive relationship between PTM and DB (r = 0.98; p < 0.001), while the correlation between physiological and morphological parameters was weak. Thus, PCA and correlation analysis proved effective in identifying superior rice varieties based on seed viability and vigor traits, potentially supporting variety selection in rice seed management and development.